Management of insects pests in storage for preservation of Cucumeropsis mannii seeds - NGWANMA U. UMA, A.A. ADEKUNLE and (Indian Phytopathology, 2004)
The preservation of Cucumeropsis mannii Naud-Holl (‘Egusi’ melon) seeds by manipulating the temperature, relative humidity and type of storage was carried out. Fungi were pathogenic on melon seeds stored at high relative humidities of 100% and 91%, but not at lower humidity between 0 and 55%. Disease manifested on the melon seeds at temperature of 20°C and 37°C whereas no disease incidence was observed at temperatures 5-10°C and 40°C. Disease incidence varied with storage condition. Seeds stored in the oven (40°C±2; R.H. 0%) had no fungal isolate after 12 months storage. Those seeds stored in the garden (27-33°C; R.H. 76-90%) and laboratory shelf (28°C-30°C; R.H. 80-87%) for the same period had fungal isolates which were absent in the beginning of storage. There was an increase in the percentage infectivity of the melon seeds as the storage period increased, for seeds stored in the garden and laboratory. Seeds stored in the oven were not infected at the end of 12 months storage period. Unshelled melon seeds were less infected with fungi when compared to shelled seeds.